Comportamiento fenológico del árbol Elaeagia uxpanapensis (Rubiaceae), en un bosque pluvial premontano de Costa Rica - Brenes Cambronero, Liz (2001)
Phenology of the tree Elaeagia uxpanapensis was studied from March 1994 to March 1998. This species is a canopy emergent in the A.M. Brenes Biological Reserve, Alajuela, Costa Rica. Fifteen mature trees were marked in order of appearance and observed every month using binoculars. A platform was built on one tree to better distinguish the transition from flowering to fruiting. Leaf abscission and budding were continuous throughout the year with several peaks, while flowering and fruit production occurred every 28 and 25 months, respectively. Leaf-fall was positively correlated with air temperature (n = 13, r = 0.44, p < 0.05), and fruiting with precipitation (n = 13, r = 0.37, p < 0.05) and relative humidity (n = 13, r = 0.39, p < 0.05). Bud formation was inversely associated with precipitation (n = 13, r = -0.66, p < 0.05) and relative humidity (n = 13, r = -0.61, p < 0.05).